Peta Literasi Media Pemilih Pemula di Surabaya - Agatha Winda Setyarinata; Theresian Intan (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2021)
This research aims to map the level of media literacy among first voters in Surabaya. 300 first-time voters were participated in this research. They are range 17 to 20 years old. The result shows that majority of first-time voters are in technical skill level. This means that they are savvy in seeking information about election through browser (2.99) as well as in saving the webpage (3.11). They are also savvy in sharing information about election (3.04) as well as in reporting the false content (3.03). The first-time voters are also literate to content about election that spread all over the internet (critical abilities). They are able to distinguish the election news which contain hoax (3.20). They are also able to verify the credibility of the news they read (2.89). The first-time voters have remark the credible sources that they trust (2.98). Although they are savvy in technical skills level and in critical abilities level, they do not adopt the communicative abilities. This means they do not participate in creating written content (1.74) and visual/audio-visual content (1.68) about the election. They tend to not repost and add caption to a content about election (1.98).